PERIODONTAL MICROCIRCULATION DURING PROSTHETICS WITH TEMPORARY BRIDGES - Pardaev D. S.; Rashidov R. A.; Said Kamil K.; Dadabaeva M. U. (Galaxy International Interdisciplinary Research Journal, 2022)
Occlusal disorders are a risk factor for the development of focal inflammatory and destructive processes in periodontal tissues, significantly worsening the course and prognosis of generalized periodontitis [1, 7]. According to I. Lebedenko et al. , the assessment of static and dynamic occlusion directly in the oral cavity (PR) is difficult, sometimes accompanied by errors. The study of models correctly installed in the articulator allows you to confirm or refute the data of the intraoral examination. This is necessary when planning combined periodontal, orthodontic and restorative treatment, reduces the time of clinical admission and reduces the amount of ground tissue [7].